Diagnostic accuracy of metagenomic next-generation sequencing for cryptococcosis in immunocompetent and immunocompromised patients - Su, Yi; Miao, Qing; Li, Na; Hu, Bi-jie; Pan, Jue (Frontiers in Cellular and Infection Microbiology, 2022)
Objective To compare the diagnostic accuracy of metagenomic next-generation sequencing (mNGS) for cryptococcosis in patients with different immune statuses with that of conventional detection. Methods A total of 1442 specimens including 71 specimens from patients with cryptococcosis were analyzed in the study. The chi square test was used to screen the sensitivity and specificity of different detection methods for different specimen types. One-way ANOVA was used to compare the mNGS results with age, CD4, lymphocytes, IFN, IL-6, IL-2 and serum antigen assay. Results The sensitivity of mNGS was 44.29% in Cryptococcus infection cases. The positive rate of mNGS results for bronchoalveolar lavage fluid (BALF, 87.50%) from immunocompromised patients was higher than that of BALF from immunocompetent patients (40.00%, p=0.04). The sensitivity of the serum Cryptococcus capsular antigen assay was 80.00% in immunocompetent patients and 96.42% in immunocompromised patients (p = 0.049). A positive rate of detection of Cryptococcus from mNGS was higher when cryptococcal antigen ≥1:160 (p=0.022) in immunocompromised patients. A positive rate of detection of Cryptococcus from mNGS was higher when lymphocyte counts were lower in both immunocompetent patients(p=0.017) and in immunocompromised patients(p=0.029). Conclusions The sensitivity of mNGS is lower than that of serum cryptococcal antigen assay and histopathology in immunocompetent patients. However, BALF detection is recommend for immunocompromised patients compared with tissue and CSF. The positive mNGS result was correlated with lower lymphocyte counts, higher IL-2 and higher serum antigen assay in immunocompromised patients.